2003
DOI: 10.1590/s0100-84042003000300014
|View full text |Cite
|
Sign up to set email alerts
|

Ontogênese do sistema subterrâneo de Pachyrhizus ahipa (Wedd.) Parodi (Fabaceae)

Abstract: -(Ontogeny of the subterranean system of Pachyrhizus ahipa (Wedd.) Parodi (Fabaceae)). A study on the ontogeny of the underground system of P. ahipa was held with the purpose of understanding both its morphology and its process of tuberization. Samples, collected from the hypocotyl region and from the primary root during different phases of plant development, were processed according to usual technic. The underground system of P. ahipa is composed by both a xylopodium and a tuberous root. The xylopodium is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…The first stage corresponds to a typical primary structure, in which the number of xylematic poles plays an important role. Milanez and Moraes-Dallaqua (2003) and Hayward (1953), among others, observed interspecific and, even, intraspecific variability in pole number. The same behavior was observed in the species analyzed in the present research, with the exception of Zornia, in which the diarch root was found to be a constant characteristic.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The first stage corresponds to a typical primary structure, in which the number of xylematic poles plays an important role. Milanez and Moraes-Dallaqua (2003) and Hayward (1953), among others, observed interspecific and, even, intraspecific variability in pole number. The same behavior was observed in the species analyzed in the present research, with the exception of Zornia, in which the diarch root was found to be a constant characteristic.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on legumes have demonstrated not only the diversity in the origin of the cambium (Carlquist, 2001;Metcalfe and Chalk, 1983) but also the occurrence of different cambial types, ranging from normal to more complex ones (Basconsuelo, 2004;Islam et al, 2007;Kraus and Basconsuelo, 2009;Kraus et al, 2003;Kraus et al, 2007;Kutschera and Lichtenegger, 1992;Lachaud et al, 1999;Milanez and Moraes-Dallaqua, 2003;Pate et al, 1989;Rajput et al, 2006;Rajput, 2003). In general, the majority of studies on legumes relate root anatomy to the environment rather than to systematics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, three types of underground organs could be identified in the same genus and tribe of the Asteraceae, showing their morphological diversity. The occurrence of xylopodia has been recorded in Brazilian Cerrado species belonging to different taxa (Appezzato-da-Glória and Estelita, 2000;Milanez and Moraes-Dallaqua, 2003), including Asteraceae representatives (Paviani, 1987(Paviani, , 1977. In some species, the lower portion of the xylopodium is joined to the upper portion of the tuberous root, as in Mandevilla illustris, M. velutina (Appezzato-da-Glória and Estelita, 2000), and Pachyrhizus ahipa (Milanez and MoraesDallaqua, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This species is characterised by the starch accumulation (of industrial interest) in its tuberous root, and the presence of rotenone in its seeds and leaves. The root is almost exclusively consumed raw as a fruit or even cooked; its skin lifts off quite easily from the internal portion, which is fleshy and mostly white (Milanez & Moraes-Dallaqua, 2003). References to ahipa root industrialisation are rather scarce, although this kind of plant has been studied by different research groups, showing its worldwide interest (Leidi et al, 2003;Leonel, Bortolucci Ferrari, Sarmento, & Alvares de Oliveira, 2005;Leonel, Sarmento, Cereda, & Camara, 2003;López et al, 2010).…”
Section: Introductionmentioning
confidence: 99%